Bidirectional associations between maternal controlling feeding and food responsiveness during infancy - Sally G. Eagleton; Lenka H. Shriver; Cheryl Buehler; Laurie Wideman; Esther M. Leerkes (Frontiers Media S.A., 2022)
Parental controlling feeding styles and practices have been associated with greater food-approaching appetitive behaviors (i.e., food responsiveness) linked to childhood obesity. Recent longitudinal research suggests that this relationship may be reciprocal such that controlling feeding predicts child appetite and vice versa. However, to date no studies have considered these associations during infancy. The current study investigates prospective bidirectional associations between controlling feeding (restriction, pressure, and food to soothe) and infant food responsiveness. Mothers (N = 176) reported their controlling feeding and their infant's food responsiveness at infant age 2, 6, and 14 months. A 3-wave cross-lagged panel model was used to test the effect of controlling feeding at an earlier time point on infant food responsiveness at a later time point, and vice versa. Maternal controlling feeding and infant food responsiveness showed moderate stability across infancy. Net of covariates, we observed parent-driven prospective relations between pressuring feeding styles and food to soothe with infant food responsiveness. Pressuring to finish was a significant predictor of increases in food responsiveness from 2 to 6 months (p = 0.004) and pressuring with cereal was a significant predictor of increases in food responsiveness from 6 to 14 months (p = 0.02). Greater use of situational food to soothe was marginally associated with higher food responsiveness from 2 to 6 months (p = 0.07) and 6 to 14 months (p = 0.06). Prospective associations between restrictive feeding styles and infant food responsiveness were not observed. Findings point to pressuring feeding styles and food to soothe as potential early life intervention targets to prevent increases in food responsiveness in infancy. Longitudinal research with follow-up in the toddler and preschool years are needed to understand how these associations unfold over time and whether child-driven effects of food responsiveness become apparent as children get older.